The political culture of New Granada, 1770-1815 - Garrido, M (1990)
This thesis is a study of New Granadan political culture during the late colonial period (1770- 1810) and the first years of Independence, known as Patria Boba (1810-1815). The study focuses on the political experiences and perceptions of three distinguishable social groups: the educated Creoles, the ordinary vecinos and the hispanicized Indians. The geographical area covered is the territory of the Audiencia of Santa Fe, which roughly corresponds to present day Colombia. A combination of ideas and experiences shaped the Creole sense of order and identity. Family clans, intellectuals, bureaucrats, lawyers and merchants built networks that found a political use on the eve of Independence and during the Patria Boba. Their notions of themselves and the other social groups, their assessment of the country's resources and their perceptions of the authorities are examined. The humbler vecinos participated in local-level politics through the election of mayors and through the process of improving their township status in the Spanish colonial hierarchy of settlements. Their notions of authority, justice, equality and belonging provide an explanation for their attitudes and allegiances during the Patria Boba. Hispanicized Indians also took part in local politics and criticized the authorities and the clergy. They attempted to influence the appointment of rulers for their communities and to preserve their land. Their sense of identity, feeling of community, and perception of outsiders are visible in their complaints and petitions. Finally, their response to the Patria Boba has particular nuances. The documents examined for the colonial period show a number of forms of local political life and suggest that it was more lively and regular than has been supposed. It is also apparent that political types and practices, until now considered distinctive features of republican culture, had colonial antecedents.